Physical properties of RIr3 (R = Gd, Tb, Ho) compounds with coexisting polymorphic phases. Issue 31 (24th July 2019) - Mondal, Binita; Dan, Shovan; Mondal, Sudipta; Bhowmik, R. N.; Ranganathan, R.; Mazumdar, Chandan
Abstract : The binary compounds GdIr3, TbIr3 and HoIr3 are synthesized successfully and found to form with macroscopic co-existence of two polymorphic phases: AuBe5 (C15b) and AuCu3 -type. Abstract : The binary compounds GdIr3, TbIr3 and HoIr3 are synthesized successfully and found to form with macroscopic co-existence of two polymorphic phases: AuBe5 (C15b) and AuCu3 -type. The dc magnetization and heat capacity studies confirm that the C15b phase orders ferromagnetically, whereas the AuCu3 phase remains paramagnetic down to 2 K. The frequency dependent ac-susceptibility data, time dependent magnetic relaxation behavior and magnetic memory effect studies suggest that TbIr3 and HoIr3 are cannonical spin-glass systems, but no glassy feature could be found in GdIr3 . The critical behavior of all three compounds has been investigated using the magnetization and heat capacity measurements around the transition temperature ( T C ). The critical exponents α, β, γ and δ have been estimated using different techniques such as the Arrott–Noakes plot, Kouvel–Fisher plot and critical isotherm as well as analysis of specific heat data and study of magnetocaloric effect. The critical analysis study identifies the type of universal magnetic class in which the three compounds belong.